Fecal transplantation: passing fashion or here to stay? - Pitt, Tyrone L. (Clinical and Biomedical Research, 2014)
Several trillions of bacteria, distributed among more than 1,000 species, are natural inhabitants of the human intestinal tract and constitute what is now known as the gut microbiota. Although its composition varies within and between individuals with age, diet, and health status, it is becoming increasingly recognized that imbalances in the bacterial microbiota (dysbiosis) are linked to a number of conditions such as antibiotic-associated diarrhea, inflammatory bowel disease, and obesity, among others. Fecal transplantation where a preparation of stool from a microbiologically screened- donor is administered into the colon of an affected recipient has been shown to be highly effective for the treatment of recurrent Clostridium difficile infection. Several trials of this therapy are now underway for gut dysbiosis in a number of patient disease groups raising concerns on the risk of transmission of infectious agents from donor to recipient, possible long-term adverse consequences of treatment, and effective regulation of the stool material used for the procedure. A worrying aspect is the emergence of private stool banks providing samples to the general public for self-administration.